2018
DOI: 10.1002/jcb.27180
|View full text |Cite
|
Sign up to set email alerts
|

miR‐384 suppressed renal cell carcinoma cell proliferation and migration through targeting RAB23

Abstract: microRNAs (miRNAs) are noncoding, short, and endogenous RNAs that play crucial roles in tumor progression at the post‐transcriptional level. Here, we studied the role of miR‐384 in the pathogenesis of renal cell carcinoma (RCC). We demonstrated that miR‐384 expression was downregulated in the RCC specimens compared with nontumor specimens. Moreover, we showed that RAB23 expression was upregulated in the RCC tissues compared with nontumor tissues. Furthermore, we demonstrated that low expression of miR‐384 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Overall, these results suggest that circPAPPA exerts its regulatory function by sponging miR-384. miR-384 has been reported to be down-regulated in multiple human cancers, suggesting that it has a tumor-suppressive role [16,17]. However, the role of miR-384 in PE had not been investigated previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results suggest that circPAPPA exerts its regulatory function by sponging miR-384. miR-384 has been reported to be down-regulated in multiple human cancers, suggesting that it has a tumor-suppressive role [16,17]. However, the role of miR-384 in PE had not been investigated previously.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that miR-384 acts as a tumor suppressor and can inhibit cell proliferation and invasion in various tumors [16][17][18]. However, there has been no similar report of its involvement in PE.…”
Section: Overexpression Of Mir-384 Inhibited Trophoblast Cell Prolifementioning
confidence: 99%
“…Differentially, expression of miR-384 was diagnosed in multiple cancers, for instance, overexpression of miR-384 inhibited gastric cancer cell growth, migration, and invasion by interacting with metadherin [ 32 , 33 ]. In addition, miR-84 suppressed cell proliferation, migration, and metastasis in renal cell carcinoma and colorectal cancer by targeting and interacting with RAB23 and KRAS/CDC42 axis, respectively [ 34 , 35 ]. Promotion of miR-384 was indicated to inhibit cell growth and EMT by sponging lncRNA TUG1 in nasopharyngeal carcinoma [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, bioinformatics prediction, luciferase reporter gene assay and RIP assay were performed to con rm the directly negative correlation between DUXAP8 and miR-384. Previous studies have revealed that miR-384 is downregulated and functions crucial roles as a tumor suppressor in a series of human cancers including renal cell carcinoma [37], osteosarcoma [38], and colorectal cancer [16]. In addition, miR-384 is also signi cantly downregulated in laryngeal cancer tissues and knockdown of miR-384 promotes the progression of laryngeal cancer through targeting WISP1 signaling pathway [19].…”
Section: Discussionmentioning
confidence: 99%